A COMPARATIVE STUDY OF HIGH SENSITIVITY C-REACTIVE PROTEIN (HS-CRP) AND GLYCEMIC MARKERS IN TYPE 2 DIABETES MELLITUS: High Sensitivity C-Reactive Protein and Glycemic Markers - Imran, Shehar Bano; Dildar, Shabnam; Taj, Sadia; Khanum, Afshan; Ahmed, Qasim (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the relationship between high sensitivity CRP (hs-CRP) and glycemic markers in samples of individuals with diabetes. Study Design: Cross sectional study. Place and Duration of Study: Fatima Memorial Hospital Lahore, from Feb to Aug 2019. Methodology: Consecutive patients aged 18-65 years coming for screening of diabetes mellitus (DM) were included. Blood sample for plasma glucose and glycated hemoglobin (HbA1c), high sensitivity CRP (hs-CRP) were analyzed. Results: Total 93 subjects were included, out of which 42 (45.2%) were males and 51 (54.8%) were females with the mean age of 48.3 ± 12 years and 42.6 ± 14 years respectively. Median concentration of hs-CRP in males and females was 0.7 (IQR1.2) mg/L and 0.6 (IQR1.4) mg/L (p-value=0.844) respectively. A significant positive correlation was observed between hs-CRP levels, HBA1c with r=0.205 (p=0.05) and fasting plasma glucose (FPG) with r=0.225 (p=0.03). However, no significant relationship was found between hs-CRP and age, BMI, waist circumference and systolic blood pressure (SBP) and diastolic blood pressure (DBP), cholesterol, LDL-cholesterol, triglycerides (TG), HDL-cholesterol. Conclusion: HbA1c and fasting plasma glucose is significantly associated with hs-CRP. This implies a significant relation between inflammation and glycemic markers. This leads to the conclusion that patients with diabetes and high hs-CRP need further evaluation, follow-up and therapy for inflammation compared to those with low hs-CRP.